Tailored Success: Disability and the Possibility of Being Successful. - Szafran, Joanna; Magdalena Wasielewska, Magdalena Wasielewska (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The article addresses the issue of success in the context of people with disabilities. Attention was paid to the specific nature of the concept; starting with the definition, attempts were made to point out that success, being a certain “objective” construct, has a definitely individual character and should be considered as such. This individual dimension designates not only the interpretative framework determining its achievement, but also draws attention to the fact that success may have many faces. There is a need for achievement in every person, a completed challenge gives a sense of happiness, and this, according to many, is the real measure of success.